Profiling the cytotoxicity of deep eutectic solvent systems and their potential applications as anticancer agents / Yves Paul Vincent Mbous - Yves Paul, Vincent Mbous (2017)
The natural origin of natural deep eutectic solvents (NADESs) primary constituents presumes negligible toxicity profiles comparing to DESs. As NADESs have become the subject of elaborate research in various sectors, it is imperative for them to be accurately established as safe mixtures. To meet this end, binary and ternary NADES systems prepared using choline chloride salt with several hydrogen bond donors-HBD (i.e., fructose, glucose, sucrose, ethylene glycol, glycerol, urea and malonic acid) were assessed in vitro using the human cervical adenocarcinoma (HelaS3), the human prostate (PC3), the human skin melanoma (A375), the human breast adenocarcinoma (MCF-7), the human gastric adenocarcinoma (AGS) and the human hepatic cell lines (WRL-68); and in vivo using ICR mice model. Concomitantly, binary DES systems were prepared using N,N-diethylethanol ammonium chloride salt and ethylene glycol, glycerol, urea, malonic acid and zinc chloride as HBDs for comparison. The results revealed that in vitro NADES systems including the water-based ternary (127 ≤ EC50 ≥ 483 mM) and binary (15 ≤ EC50 ≥ 1260 mM) were on average less toxic than binary DES systems (34 ≤ EC50 ≥ 120 mM). The negligible cytotoxicity profiles of NADESs compared to standard DESs stem from the natural origin of their constituents especially those of metabolic importance. It was also found that NADESs prepared using fructose, glucose or glycerol had lesser detrimental effect as opposed to solvents prepared using organic acids malonic acid or zinc chloride. A trend between the cellular requirements of cancer cells, the viscosity of ternary NADESs and their cytotoxicity was observed. High viscosities correlated with higher cytotoxicity. Further, the presence of water in ternary NADESs yielded less potent mixtures. Results also showed that the longer alkyl chain of the N,N-diethylethanol ammonium chloride salt -used for DESs preparation- significantly increased their cytotoxicity in contrast with choline chloride based-NADESs even when the same HBDs (glycerol, ethylene glycol and urea) had been used to prepare both types of mixtures. It was discovered for the first time that binary NADESs are synthesized intracellularly to counterbalance the individual cytotoxicity of the chief materials; thus, making NADES the possible third liquid phase in mammalian cells and a potential tool for physiology-based work. Further, binary NADESs seemed to induce necrosis through increasing membrane porosity and redox stress. However, binary NADESs were, in vivo, more destructive than binary DESs and caused liver failure. The first time application of the Conductor-like Screening Model for Real Solvent (COSMO-RS) model for cytotoxic studies was demonstrated through the simulation of the interactions taking place between NADESs/DESs and cellular membranes. The results suggested that the accumulation and aggregation of these mixtures on the lipid bilayers defined their cytotoxicity. The selectivity index (i.e., EC50 ratio of cancer to healthy cell line) values of ternary and binary NADES systems (0.24 ≤ SI ≥ 1.061) were lower than those of binary DES systems (0.269 ≤ SI ≥ 1.315), implying that DESs were more active as anticancer material compared with NADESs, thereby reinforcing the conclusion that they are indeed more cytotoxic than the naturally synthesized NADESs.